Transcriptional Responses of Candida albicans to Antimicrobial Peptide MAF-1A - Wang, Tao; Xiu, Jiangfan; Zhang, Yingchun; Wu, Jianwei; Ma, Xiaolin; Wang, Yu; Guo, Guo; Shang, Xiaoli (Frontiers in Microbiology, 2017)
Candida albicans is a major fungal pathogen in humans. Novel antifungal agents are urgent demanded due to the challenges of the resistance. Antimicrobial peptides are critical components of the innate immune system against pathogenic microorganism infection. MAF-1A is a novel cationic antimicrobial peptide that comes from Musca domestica and is effective against C. albicans, but the antifungal mechanism remains unclear. In this study, we performed a transcriptomics analysis in C. albicans using RNA-seq technique under the treatment of MAF-1A. A total of 5654 genes were identified. Among these, 1032 were differentially expressed genes (DEGs), including 575 up-regulated genes and 457 down-regulated genes. In these DEGs, genes encoding ergosterol metabolism and fatty acid biosynthesis were identified to be significantly down-regulated, while genes associated with oxidative stress response and cell wall were identified to be significantly up-regulated. Using pathway enrichment analysis, 12 significant metabolic pathways were identified, and ribosome, oxidative phosphorylation, citrate cycle were mainly involved. The results revealed that MAF-1A induces complex responses in C. albicans. This study provides evidence that MAF-1A may inhibit the growth through affect multi-targets in C. albicans cells.